Osteochondroma of rib cage in a case of HME: A rare presentation - Saroj prasad Sah; Vikas Maheshwari; Aditya K.S. Gowda; Bom Bahadur; Robin Yadav; Mohit Dhingra (Journal of Orthopaedic Reports, 2023)
Background: Osteochondroma is the most common benign bone tumor. This aberrant developmental lesion of the bone in the rib is rare and forms part of multiple diaphyseal aclasia in some cases. Large osteochondroma of the ribs has a high chance of converting into malignancy and surgical excision forms the only option for the management. Presentation of case: A 20yr male with hereditary multiple exostoses was referred to us for swelling of the left side of the chest which was gradually increasing in size. Due to progressively enlarging size and suspicion of malignant transformation, the surgical excision was planned, though the lesion was asymptomatic. Surgical excision was done along with the part of the rib. The per-op and post-op period of the patient was uneventful. Conclusion: Asymptomatic osteochondroma should be put on closed follow-up if the lesion is present and is not showing any growth in size. Large tumours with suspicion should be removed along with the part of the rib.